Effect of antibiotic growth promoters (AGPs) on feed conversion ratio (FCR) of broiler chickens: A meta-analysis - Mohamed El-Fateh; Muhammad Bilal; Xin Zhao (Poultry Science)
Antibiotics have been used for a long time as growth promoters in the poultry industry for growth and health benefits. However, recent studies reflected little, no, or negative impacts of using antibiotics for growth promotion purposes. This study was designed to examine the overall effect of antibiotic supplementation on the feed conversion ratio (FCR) in broiler chickens as a performance indicator and assess different covariates for explaining heterogeneity in response to the use of antibiotics as growth promoters. In this regard, FCRs obtained from articles that compared diets with and without antibiotics for broiler chickens were extracted from electronic databases (PubMed, Web of Science, and Google Scholar) as per PRISMA guidelines. The database comprised 42 scientific articles containing 74 experiments totaling 19,562 chickens. A basic meta-analysis and subgroup analysis were performed to assess the overall impact of antibiotic growth promoters (AGPs) on FCR of broiler chickens while a meta-regression analysis was used to assess different covariates (breed, antibiotic dose, location, time, presence of anticoccidial in the feed, antibiotic type, and housing type) to explain variations in true effect size of the studies. The basic meta-analysis of these studies revealed an overall improvement in FCR by 2.8 % (p < 0.05) due to addition of AGPs than the control group with the confidence interval range from 1.3 to 4.3 % and the prediction interval ranging between -10 and 16 %. The covariates, including breed, dose and location, provided the optimum model fit and explained 53 % of variations in the FCR across different studies. In summary, an overall marginal improvement has been observed in mean FCR of broiler chickens along with a wide range of variations in response to use of AGPs. The variations in true effects among these studies are subject to several confounding effects, particularly breed, dose and location. Considering the marginal positive effect of antibiotic usage in chicken performance, we recommend against using of AGP.